Rome and the classic Maya - Storey, Rebecca, 1950-, author.
1 online resource (xi, 280 pages)
Keywords: "This volume compares two of the most famous cases of civilizational collapse, that of the Roman Empire and the Classic Maya world. First examining the concept of collapse, and how it has been utilized in the historical, archaeological and anthropological study of past complex societies, Storey and Storey draw on extensive archaeological evidence to consider the ultimate failure of the institutions, infrastructure and material culture of both of these complex cultures"--Provided by publisher.